Silent Reading on Medium Apps to Improve Students’ Reading Comprehension Skill - Arif Prasetya; Mutiarani Mutiarani (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to analyze the effectiveness of silent reading through the use of the Medium App in improving students’ reading comprehension skills. Reading comprehension is an essential language skill that requires learners to understand, interpret, and critically analyze written texts. With the advancement of educational technology, digital applications supported by artificial intelligence—such as the Medium App—offer adaptive features that enable a more personalized and interactive reading experience. Through the silent reading method, students are given the opportunity to read at their own pace without the constraints of oral articulation, allowing for greater focus and deeper processing of meaning. Previous research indicates that silent reading assisted by digital platforms can enhance reading fluency, enrich vocabulary, and improve learning motivation. However, the integration of both approaches has rarely been examined comprehensively. This study employs a literature review approach to explore how the use of the Medium App in silent reading activities can significantly influence students’ reading comprehension. The findings highlight that the combination of silent reading strategies and adaptive technology has the potential to serve as an effective instructional method for improving literacy, particularly among intermediate English language learners.